Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

Using dispersion models at microscale to assess long-term air pollution in urban hot spots: A FAIRMODE joint intercomparison exercise for a case study in Antwerp - F. Martín; S. Janssen; V. Rodrigues; J. Sousa; J.L. Santiago; E. Rivas; J. Stocker; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; et al. (Science of The Total Environment, 2024)

Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Persistent Patterns of E. coli Concentrations in Two Irrigation Ponds from 3 Years of Monitoring - Matthew D. Stocker; Yakov A. Pachepsky; Jaclyn Smith; Billie Morgan; Robert L. Hill; Moon S. Kim (Water, Air, & Soil Pollution, 2021)

Current fluconazole treatment regimens result in under-dosing of critically ill adults during early therapy - Indy Sandaradura; Deborah J. E. Marriott; Richard O. Day; Ross L. G. Norris; Edna Pang; Sophie L. Stocker; Stephanie E. Reuter (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Intraseasonal variation of phycocyanin concentrations and environmental covariates in two agricultural irrigation ponds in Maryland, USA - J. E. Smith; M. D. Stocker; J. L. Wolny; R. L. Hill; Y. A. Pachepsky (Environmental Monitoring and Assessment, 2020)

Manure Consistency and Weathering Affect the Removal of Fecal Indicator Bacteria from Grass-Covered Soil - M. D. Stocker; R. L. Hill; Y. A. Pachepsky (Water, Air, & Soil Pollution, 2020)

The Effect of Temperature Oscillations and Sediment Texture on Fecal Indicator Bacteria Survival in Sediments - Jaclyn E. Smith; Matthew D. Stocker; Robert L. Hill; Yakov A. Pachepsky (Water, Air, & Soil Pollution, 2019)

Sodium-glucose cotransporter 2 inhibitors for type 2 diabetes—cardiovascular and renal benefits in patients with chronic kidney disease - Tamara Y. Milder; Sophie L. Stocker; Dorit Samocha-Bonet; Richard O. Day; Jerry R. Greenfield (European Journal of Clinical Pharmacology, 2019)

The effects of trehalose glycolipid presentation on cytokine production by GM-CSF macrophages - Bridget L. Stocker; Kristel Kodar; Kanu Wahi; Amy J. Foster; Jacquie L. Harper; Daiki Mori; Sho Yamasaki; Mattie S. M. Timmer (Glycoconjugate Journal, 2019)

Strengths and weaknesses of the FAIRMODE benchmarking methodology for the evaluation of air quality models - A. Monteiro; P. Durka; C. Flandorfer; E. Georgieva; C. Guerreiro; J. Kushta; L. Malherbe; B. Maiheu; A. I. Miranda; G. Santos; J. Stocker; E. Trimpeneers; et al. (Air Quality, Atmosphere & Health, 2018)

The versatility of N-alkyl-methoxyamine bi-functional linkers for the preparation of glycoconjugates - Stefan Munneke; Emma M. Dangerfield; Bridget L. Stocker; Mattie S. M. Timmer (Glycoconjugate Journal, 2017)

Visualization of coral host–pathogen interactions using a stable GFP-labeled Vibrio coralliilyticus strain - F. Joseph Pollock; Cory J. Krediet; Melissa Garren; Roman Stocker; Karina Winn; Bryan Wilson; Carla Huete-Stauffer; Bette L. Willis; David G. Bourne (Coral Reefs, 2015)

The IPCC AR5 guidance note on consistent treatment of uncertainties: a common approach across the working groups - Michael D. Mastrandrea; Katharine J. Mach; Gian-Kasper Plattner; Ottmar Edenhofer; Thomas F. Stocker; Christopher B. Field; Kristie L. Ebi; Patrick R. Matschoss (Climatic Change, 2011)

Lack of effect of hydrochlorothiazide and low-dose aspirin on the renal clearance of urate and oxypurinol after a single dose of allopurinol in normal volunteers - Daniel Y. Ng; Sophie L. Stocker; Garry G. Graham; Kenneth M. Williams; Richard O. Day (European Journal of Clinical Pharmacology, 2011)

Culture studies on the mycobiont isolated from Parmotrema reticulatum (Taylor) Choisy: metabolite production under different conditions - Alejandra T. Fazio; María D. Bertoni; Mónica T. Adler; Laura B. Ruiz; María L. Rosso; Lucia Muggia; Armin Hager; Elfie Stocker-Wörgötter; Marta S. Maier (Mycological Progress, 2009)

The influence of regional circulation patterns on wet and dry mineral dust and sea salt deposition over Greenland - M. A. Hutterli; T. Crueger; H. Fischer; K. K. Andersen; C. C. Raible; T. F. Stocker; M. L. Siggaard-Andersen; J. R. McConnell; R. C. Bales; J. F. Burkhart (Climate Dynamics, 2007)

The association between inversion In(3R)Payne and clinally varying traits in Drosophila melanogaster - L. Rako; A. R. Anderson; C. M. Sgrò; A. J. Stocker; A. A. Hoffmann (Genetica, 2006)

Response: Sustainable Forestry and Certification Programs - J. Heissenbuttel; R. Cantrell; L. Stocker (Journal of Forestry, 2001)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Link between the North and South Atlantic during the Heinrich events of the last glacial period - L. Vidal; R.R. Schneider; O. Marchal; T. Bickert; T.F. Stocker; G. Wefer (Climate Dynamics, 1999)